Dorsal Displacement of the Soft Palate Secondary to Persistent Frenulum of the Epiglottis in Neonatal Foal - Conceição, Mariana L. [UNESP]; Alonso, Juliana M. [UNESP]; Alves, Ana Liz G. [UNESP]; Hussni, Carlos A. [UNESP]; Rodrigues, Celso A. [UNESP]; Watanabe, Marcos J. [UNESP] (Elsevier, 2020)
Dorsal displacement of the soft palate (DDSP) usually occurs in athletic adult horses. Congenital DDSP in foals secondary to the persistent frenulum of the epiglottis is rarely observed. The aim of this report was to describe a case of a seven-day-old female neonate Quarter Horse presenting dysphagia, milk reflux through the nostrils and mouth, and expiratory dyspnea since 4 days. Thoracic auscultation was indicative of aspiration pneumonia. Diagnosis of DDSP associated with local inflammation was made after endoscopic examination of upper respiratory tract. Radiographic examination was performed to rule out hypoplasia of the epiglottis. No clinical improvement was observed after anti-inflammatory treatment with flunixin meglumine. Oral endoscopy under general anesthesia revealed that the displacement of the soft palate was caused by a persistent frenulum of the epiglottis. Using a 30° rigid endoscope and a curved laparoscopic scissors, the frenulum was transected. After surgery, no dysphagia or dyspnea at rest was observed. However, discreet respiratory noise persisted during exercise for 5 days postoperatively. After discharge, the owner reported that the animal was completely normal during exercise. The animal is currently 3 years old and is developing a normal athletic performance. Persistent frenulum of the epiglottis should be considered while examining neonates with nasal milk reflux associated with expiratory dyspnea. This case report emphasizes the importance of the differential diagnosis for DDSP and for DDSP secondary to the persistent frenulum of the epiglottis in neonatal foals. It also underlines the importance of oral endoscopic examination for diagnosis.
Keywords: Congenital diseases; Endoscopic surgery; Horses; Respiratory noise